Evaluation of the physical properties of the Iranian temporary cement, Tem Band, and the foreign one, Temp Bond, compared to ISO 3107 - Soltan Karimy V.; Bayanzadeh SM (Tehran University of Medical Sciences, 2006)
Background and Aim: Iranian temporary cement, Tem Band, has been manufactured by Golchai company, and introduced to market as a suitable material but its properties have not been tested yet. The aim of this study was to investigate the setting time, film thickness, compressive strength, disintegration and arsenic content of Tem Band and Temp bond temporary cements and compare them to ISO 3107. Materials and Methods: In this experimental study, 12 samples from each cement were obtained and setting time, film thickness, compressive strength, solubility and disintegration were tested according to ISO 3107. In addition, arsenic content was tested based on ASTM 6052. Data were analyzed with t-test and p<0.05 was considered as the limit of significance. Results: The average setting time of Tem Band was 5 minutes and 47 seconds (4.17 minutes for Temp Bond), the average film thickness was 6.67 micrometer for Tem Band and 4.08 micrometer for Temp Bond. There was no difference between two cements regarding setting time and film thickness and for both was at the standard range. Compressive strength of Tem Band was 5.67 MPa and 8.5 MPa for Temp Bond. The difference was statistically significant but for both cements was less than standard (35 MPa). There was no significant difference regarding the solubility and disintegration tests. In both samples, the solubility and disintegration values were in standard ranges. Both cements did not contain arsenic but lead level was at the maximum standard range in Tem Band. Conclusion: Considering these results, both cements are applicable to different clinical situations based on their physical properties. Studies on the biocompatibility of the Iranian cement is recommended.